2020
DOI: 10.3390/polym12020265
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Interaction Enhanced Rheological Behavior in PAM/CTAC/Salt Aqueous Solution—A Coarse-Grained Molecular Dynamics Study

Abstract: Interfacial interactions within a multi-phase polymer solution play critical roles in processing control and mass transportation in chemical engineering. However, the understandings of these roles remain unexplored due to the complexity of the system. In this study, we used an efficient analytical method—a nonequilibrium molecular dynamics (NEMD) simulation—to unveil the molecular interactions and rheology of a multiphase solution containing cetyltrimethyl ammonium chloride (CTAC), polyacrylamide (PAM), and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…The high shear viscosity of binary additives is attributed to the network-link composite structure by the interaction and bridge effect of Alg-DA chains and APG micelles. 40,41 More precisely, the interaction improves the antishear performance of Alg-DA/APG, and the bridge effect strengthens the network-link structure of composite micelles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high shear viscosity of binary additives is attributed to the network-link composite structure by the interaction and bridge effect of Alg-DA chains and APG micelles. 40,41 More precisely, the interaction improves the antishear performance of Alg-DA/APG, and the bridge effect strengthens the network-link structure of composite micelles.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with Alg-DA, the binary additive Alg-DA/APG not only shows a similar shear-thinning property of the non-Newtonian fluid but also exhibits higher shear viscosity. The high shear viscosity of binary additives is attributed to the network-link composite structure by the interaction and bridge effect of Alg-DA chains and APG micelles. , More precisely, the interaction improves the antishear performance of Alg-DA/APG, and the bridge effect strengthens the network-link structure of composite micelles.…”
Section: Resultsmentioning
confidence: 99%
“…Related to the drug‐delivery applications but also of relevance for other technological uses, several Martini‐based works studied how small molecules (such as drugs or surfactants) self‐assemble with polymers or diffuse into polymer matrices. [ 145–154 ] In one study, Sharma and Dormidontova investigated the formation of polymer‐wrapped and polymer‐threaded worm‐like micelles as a function of polymer hydrophobicity and rigidity. [ 151 ]…”
Section: Example Applicationsmentioning
confidence: 99%
“…These initial seeds or nanostructures generated for performing SAXS-guided coarse-grained Monte Carlo (CGMC) simulations are derived from the results of various characterization and simulation studies reported previously in the literature. [40][41][42][43][44][45][46][47][48][49] Specifically, sixty-five geometries are considered for seeding the nanostructures to the developed SAXS-guided sampling scheme. The basis for screening these sixty-five geometries originates from the known information that the characteristic length of a DBC is a few hundreds of nanometers.…”
Section: Seeding Saxs-guided Nanostructures To Unbaised Cgmcmentioning
confidence: 99%